Pseudomonas HopU1 modulates plant immune receptor levels by blocking the interaction of their mRNAs with GRP7 - Nicaise, Valerie (European Molecular Biology Organization, 2013)
Pathogens target important components of host immunity to cause disease. The Pseudomonas syringae type III-secreted effector HopU1 is a mono-ADP-ribosyltransferase required for full virulence on Arabidopsis thaliana. HopU1 targets several RNA-binding proteins including GRP7, whose role in immunity is still unclear. Here, we show that GRP7 associates with translational components, as well as with the pattern recognition receptors FLS2 and EFR. Moreover, GRP7 binds specifically FLS2 and EFR transcripts in vivo through its RNA recognition motif. HopU1 does not affect the protein–protein associations between GRP7, FLS2 and translational components. Instead, HopU1 blocks the interaction between GRP7 and FLS2 and EFR transcripts in vivo. This inhibition correlates with reduced FLS2 protein levels upon Pseudomonas infection in a HopU1-dependent manner. Our results reveal a novel virulence strategy used by a microbial effector to interfere with host immunity.